ANALISIS PERTIMBANGAN HUKUM HAKIM DALAM PERKARA SENGKETA HAK ATAS TANAH PUTUSAN NOMOR 69/PDT.G/2022/PN PTK - NIM. A1011201158, NURHIDAYAH WISNU RAHMAN (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstrac The issue of land rights dispute arose when Ms. Rajemah Binti Said sold a plot of land of 115 square meters in the Sekip Land Ground so that the son of Ms. Rajemah Biti Said eventually brought this case to the court because they judged that they had the right to the land and considered the sale of land carried out by Mrs. Rajamah Bitti Said unlawful according to the law with the accusation of the absence of the law so that there was a problem of the dispute of the land rights. The title of this research is Analysis of Judges' Legal Considerations in Land Rights Dispute Cases Decision Number 69/PDT.G/2022/PN PTK, the formulation of the problem